2021
DOI: 10.1007/s10664-020-09903-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to manage quality requirements in agile software development: a multiple case study

Abstract: Agile methods can deliver software that fulfills customer needs rapidly and continuously. Quality requirements (QRs) are important in this regard; however, detailed studies on how companies applying agile methods to manage QRs are limited, as are studies on the rationale for choosing specific QR management practices and related challenges. The aim of this study was to address why practitioners manage QRs as they do and what challenges they face. We also analyzed how existing practices mitigate some of the foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Other targets are improved quality (e.g. Chakravarty et al 2021;Dybå and Dingsøyr 2008;Karhapää et al 2021;MnKandla et al 2006), and better innovation performance (e.g. Highsmith and Cockburn 2001;Kettunen 2007;Ravichandran 2018;Teece et al 2016;Wilson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other targets are improved quality (e.g. Chakravarty et al 2021;Dybå and Dingsøyr 2008;Karhapää et al 2021;MnKandla et al 2006), and better innovation performance (e.g. Highsmith and Cockburn 2001;Kettunen 2007;Ravichandran 2018;Teece et al 2016;Wilson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other targets are improved quality (e.g. Chakravarty et al 2021;Dybå and Dingsøyr 2008;Karhapää et al 2021;MnKandla et al 2006), and better innovation performance (e.g. Highsmith and Cockburn 2001;Kettunen 2007;Ravichandran 2018;Teece et al 2016;Wilson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that agile development reduced the cost of system development which includes testing, and also enhanced IT -business alliances (Tarhini, Yunis & El-Kassar, 2018). One major comparative advantage of the agile development process is that it delivers software that fulfils customer needs rapidly and continuously (Karhapää et al, 2021).…”
Section: Comparison Between Traditional and Agile Approach Towards Software Developmentmentioning
confidence: 99%